Teacher Creativity and Students’ Comprehension of Religious Values: Evidence from Inclusive Education - Adiyono, Adiyono; Patimah, Lilis; Malik, Abdul; Abdurrohim, Abdurrohim (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Education for students with intellectual disabilities poses unique Education for students with intellectual disabilities poses unique challenges, particularly when teaching abstract subjects such as Islamic values, which encompass ritual, moral, and ethical dimensions. Understanding how teachers’ creativity in utilizing instructional media can improve students’ comprehension of these values is crucial for advancing inclusive education practices. This study aimed to examine the relationship between teachers’ creativity in instructional media and students’ comprehension of Islamic values among students with intellectual disabilities at SLBN Tanah Grogot, Indonesia. A quantitative correlational design was employed, involving 15 students from grades VII–IX and three Islamic education teachers, selected through total sampling. Data were collected using a teacher creativity questionnaire, classroom observations, and students’ summative assessment scores in Islamic education, and were analyzed using descriptive statistics and Pearson’s product–moment correlation. The findings revealed that teachers demonstrated a very high level of creativity (mean score = 95%), characterized by the use of varied, adaptive, and interactive media that encouraged active participation. Students’ comprehension scores indicated a good level of understanding (mean = 80.93), and a strong positive correlation (r = 0.87, p < 0.05) was found between teacher creativity and students’ comprehension. These results highlight that creative use of instructional media significantly contributes to improving students’ ability to understand and apply Islamic values. The study highlights the importance of training teachers in designing inclusive and engaging media, suggesting that such approaches can improve moral education outcomes for students with intellectual disabilities. This result provides valuable insights for educators and policymakers seeking to enhance inclusive religious education globally.